Uji Toksisitas Akut Ekstrak Air Tanaman Sarang Semut (Myrmecodia pendans) Terhadap Histologi Organ Hati Mencit - Soeksmanto, Arif; Simanjuntak, Partomuan; Subroto, Muhammad Ahkam (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
erbal products in powder or capsule forms made of sarang semut plant have been widely distributed in market.This plant is believed to treat several diseases, such as cancer, gout, liver, stroke, heart, hemorrhoid, back pain,allergy, and as tonicum to increase sexual desire. Information on the plants was still limited on plant distribution,ecology, ethnobotany, and taxonomy, without research on toxicity and clinical aspect. Considering that sarangsemut products has been distributed at market and limited scientific publication of the plant, hence acute toxicitytest of sarang semut extract should be conducted. The results showed that dose of 375 mg/kg bw caused liverdegeneration on day-5 and normal on day-19. Whereas dose of 3750 mg/kg bw caused cell necrosis up to day-12,degeneration still apparent on day-26.